HANJA (2021)
HANJA is a mixed logic product that pretends to help with the memorization of Korean vocabulary from Chinese - Korean sinograms. For this reason, it was developed from two elements: a physical one, composed of 34 cards with an aesthetic function that reflect the sinograms and 35 composition cards that contain the vocabulary list, which will interact with each other so that the user has access to the element. where you will find the study and review tools. This component's main function is to reflect an elegant and delicate aesthetic, which will allow a closer relationship with the user since the acquisition will be based on attraction and not on need. This part is essential for the use of the application since the growth of the latter will only be generated if the user interacts with the physical cards and chips. The second element is a mobile application. Its aesthetics are simple, since the objective is to help the learning and develop of the vocabulary of the Korean language by means of various text, audio and video tools, both in-house and external for "massive consume". In it, various mnemonic techniques were implemented so that the user memorizes in a new and easier way, relating the knowledge that he wishes to retain with those he already knows.